North American Tunneling : 2012 Proceedings - Fowler, Matthew (Society for Mining, Metallurgy and Exploration, 2012)
North American Tunneling is the premier forum to discuss new trends and developments in underground construction in North America. With every conference, the number of attendees and breadth of topics has grown. This collection of papers presented at the highly regarded 2012 North American Tunneling Conference records many of the tremendous advances that have been made in the delivery of more cost-effective and less disruptive solutions to the underground infrastructure needs of North America. With more than 100 papers from engineers, contractors, owners, suppliers, manufacturers, and others.